ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI KECENDERUNGAN KECURANGAN AKUNTANSI - Yupianti Yupianti; Erni Yanti Natalia (J-MACC, 2023)
In the business of world, fraud or deviant behavior is often encountered, one of which is accounting fraud. Accounting fraud is an act that is against the law and is an act of dishonesty committed by someone inside or outside a company. The purpose of this study was to determine the influence of internal control, observance of accounting rules, and individual morality on the tendency toward accounting fraud. The sample used is non-probability sampling by applying a random sampling methodology to 100 company employee respondents in the departments of accounting, finance, purchasing, and the like in Batam City. Multiple linear regression analysis approaches were employed in this study's data analysis to both assess the dependent variable's dependency on each independent variable and the dependent variable's influence on the independent variables. The results of the study show that adherence to accounting rules and individual morality have a partially significant effect on the tendency toward accounting fraud. Internal control partially has no significant effect on the tendency for accounting fraud